Stemness Characteristics of Periodontal Ligament Stem Cells from Donors and Multiple Sclerosis Patients: A Comparative Study. (14th December 2017) - Diomede, Francesca; Rajan, Thangavelu Soundara; D'Aurora, Marco; Bramanti, Placido; Merciaro, Ilaria; Marchisio, Marco; Gatta, Valentina; Mazzon, Emanuela; Trubiani, Oriana
Abstract : Multiple sclerosis (MS) is the most prevalent and progressive autoimmune disease that affects the central nervous system, and currently, no drug is available for the treatment. Stem cell therapy has received substantial attention in MS treatment. Recently, we demonstrated the immunosuppressive effects of mesenchymal stem cells derived from neural crest-originated human periodontal ligament tissue (hPDLSCs) in an in vivo model of MS. In the present study, we comparatively investigated the stemness properties of hPDLSCs derived from healthy donors and relapsing-remitting MS patients. Stem cell marker expression, cell proliferation, and differentiation capacity were studied. We found that both donor- and MS patient-derived hPDLSCs at early passage 2 showed similar expression of surface antigen markers and cell proliferation rate. Significant level of osteogenic, adipogenic, chondrogenic, and neurogenic differentiation capacities was observed in both donor- and MS patient-derived hPDLSCs. Interestingly, these cells maintained the stemness properties even at late passage 15. Senescence markers p16 and p21 expression was considerably enhanced in passage 15. Our results propose that hPDLSCs may serve as simple and potential autologous stem cell niche, which may help in personalized stem cell therapy for MS patients.